Reframing STEAM in Early Childhood Education: A Qualitative Study of Its Role in Fostering Social Competence in Indonesian Kindergarten Contexts - Zahrah, Aisyatuz; Alfin Mazidah, Nur; Aini, Nur; Oktavia R., Rany; Bandara, K. M. N. T. K.; F. Uy Jr, Ricardo; Veda Saphira, Hanandita (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2026)
Background of the study: Although STEAM (Science, Technology, Engineering, Arts, and Mathematics) is widely implemented in early childhood education to enhance cognitive and creative outcomes, its contribution to social competence remains underexplored, particularly in non-Western contexts. In Indonesian early childhood settings, STEAM practices largely prioritize measurable cognitive achievement, limiting recognition of its potential as a socially mediated learning approach. Aims and scope of paper: This study aims to reconceptualize STEAM in ECE by examining how STEAM-based learning activities facilitate the development of social competence among children aged 5–6 years in an Indonesian kindergarten context. Methods: A qualitative descriptive design was employed at Annahusada Kindergarten. Data were generated through prolonged classroom observations of group-based STEAM project activities, semi-structured interviews with classroom teachers, and analysis of children’s learning documentation. The data were analyzed using thematic analysis involving systematic coding, categorization, and interpretation of recurring interactional patterns. Credibility and trustworthiness were ensured through methodological triangulation across data sources and techniques. Results: The findings indicate that STEAM learning, when structured as collaborative project-based inquiry, creates meaningful contexts for peer interaction and shared problem-solving. Three dominant dimensions of social competence emerged: cooperative behavior, communicative negotiation, and active participatory engagement. Empathic dispositions developed more progressively, particularly through role allocation, peer scaffolding, and task-related assistance. These findings position STEAM not solely as an interdisciplinary cognitive model but as a socio-constructivist learning ecology that supports interpersonal skill development. Contribution: This study contributes to the expanding discourse on STEAM in early childhood education by reframing it as an integrative pedagogical approach that simultaneously advances cognitive and social developmental objectives. By providing empirical evidence from the Indonesian context, the study enriches global STEAM scholarship and offers practical implications for designing socially responsive and culturally grounded STEAM curricula in early learning environments.